2020
DOI: 10.1111/1475-679x.12335
|View full text |Cite
|
Sign up to set email alerts
|

Resolving Information Asymmetry Through Contractual Risk Sharing: The Case of Private Firm Acquisitions

Abstract: When private firms are acquired, buyers commonly rely on seller financing and earnouts. Using a novel database of private acquisitions, I find that seller financing and earnouts become more common as information asymmetry increases between the acquirer and the target. Financial statement audits of the targets attenuate these results, which suggests that audits decrease information asymmetry in firm acquisitions. Seller-financed acquisitions also close faster and at higher prices, reducing the private firm disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(10 citation statements)
references
References 106 publications
(161 reference statements)
0
10
0
Order By: Relevance
“…Seminal papers on earnouts (Datar et al, 2001;Kohers & Ang, 2000;Ragozzino & Reuer, 2009) found that such contracts are generally used in transactions where substantial uncertainties exist about the future performance of the acquired entity, or in general about its intrinsic value. By linking part of the payment to the performance of the target following the closing of the deal, earnouts allow for an ex-post verification of the target's value, thus limiting information asymmetry issues (see also Jansen, 2020). Indeed, the authors documented that these contracts are mainly applied in the acquisition of private companies and subsidiaries, for which no market price is available to shed light on their value; in cross-industry acquisitions, where the bidder may lack sufficient expertise on the target's business and, thus, the risk of an overpayment is higher; in the acquisition of startups and in general firms with sizeable growth opportunities, or firms with large amounts of intangible assets, all cases where the uncertainties in the target's future prospects are particularly severe.…”
Section: Literature On Earnoutsmentioning
confidence: 99%
“…Seminal papers on earnouts (Datar et al, 2001;Kohers & Ang, 2000;Ragozzino & Reuer, 2009) found that such contracts are generally used in transactions where substantial uncertainties exist about the future performance of the acquired entity, or in general about its intrinsic value. By linking part of the payment to the performance of the target following the closing of the deal, earnouts allow for an ex-post verification of the target's value, thus limiting information asymmetry issues (see also Jansen, 2020). Indeed, the authors documented that these contracts are mainly applied in the acquisition of private companies and subsidiaries, for which no market price is available to shed light on their value; in cross-industry acquisitions, where the bidder may lack sufficient expertise on the target's business and, thus, the risk of an overpayment is higher; in the acquisition of startups and in general firms with sizeable growth opportunities, or firms with large amounts of intangible assets, all cases where the uncertainties in the target's future prospects are particularly severe.…”
Section: Literature On Earnoutsmentioning
confidence: 99%
“…These earnout thresholds are typically related to the target's post-acquisition performance (e.g., sales, earnings or project milestones), and the earnout period ranges from one year to more than five years (Datar et al 2001). 4 Prior studies provide substantial empirical evidence that the use of earnouts is an effective contractual mechanism to bridge a valuation gap between the target and acquirer (Barbopoulos and Sudarsanam 2012;Jansen 2020), retain target management (Cain et al 2011;Cadman et al 2014), or serve as a source of financing for constrained acquirers (Bates et al 2018). Hence, earnouts are used mostly in acquisitions of private targets or targets in certain sectors with high business uncertainty.…”
Section: Earnouts In Acquisitionsmentioning
confidence: 99%
“…Non-public acquirers are an ideal comparison group to public acquirers with respect to the use of earnouts. The ubiquitous benefits of using earnouts (i.e., mitigating valuation risk, alleviating acquirers' financial constraints) also apply to private acquirers (Jansen 2020). Nevertheless, public firms are more likely to boost short-term profitability because they face greater capital market pressures on near-term performance than do private firms (Golubova and Xiong 2020).…”
Section: Ifrs 3 (2008) and The Use Of Earnouts In Acquisitions Empirical Predictionmentioning
confidence: 99%
See 2 more Smart Citations